Policing and the Roman Empire - Couper, James Grant (Trinity College Dublin, 2007)
The Roman Empire, from the beginning of the Principate (28 BC onwards), had no full-time dedicated police force as we understand the concept. However the state had to deal with individuals and groups who were intent on threatening local law and order: thieves, cattle rustlers, murderers, bandits and their supporters.
Exhibited at the second Glucksman Memorial Symposium on June 13th 2007
Keywords: Roman Empire; Policing